2018
DOI: 10.12965/jer.1836340.170
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin improves functional recovery from sciatic crushed nerve injury in rats

Abstract: Peripheral nerve injuries are commonly encountered clinical problem and often result in chronic pain and severe functional deficit. Diosgenin is a plant steroidal saponin and has anti-inflammatory and anticancer effects. In the present study, we investigated the effect of diosgenin on functional recovery following sciatic crushed nerve injury in rats. Walking track analysis for the functional recovery which can be quantified with the sciatic function index (SFI) was conducted. Immunohistochemistry for c-Fos in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Lee et al have examined the effect of DG on chronic pain and functional deficit resulting from sciatic crushed nerve injury in rats. DG treatment increased the sciatic function index and suppressed the nerve injury-induced overexpression of BDNF, TrkB, COX-2, iNOS, and c-Fos in the ventrolateral periaqueductal gray and paraventricular nucleus, suggesting that DG treatment could prolong pain control and extended functional recovery after peripheral nerve injury [102]. 9.10.…”
mentioning
confidence: 93%
“…Lee et al have examined the effect of DG on chronic pain and functional deficit resulting from sciatic crushed nerve injury in rats. DG treatment increased the sciatic function index and suppressed the nerve injury-induced overexpression of BDNF, TrkB, COX-2, iNOS, and c-Fos in the ventrolateral periaqueductal gray and paraventricular nucleus, suggesting that DG treatment could prolong pain control and extended functional recovery after peripheral nerve injury [102]. 9.10.…”
mentioning
confidence: 93%
“…However, the protective effects of neurotrophic factors on nerves have often controversy (Zhao et al, 2015). Lee et al (2018) demonstrated that BDNF expression in the sciatic nerve was increased by SCI, in contrast, treatment with diosgenin suppressed BDNF expression.…”
Section: Discussionmentioning
confidence: 97%
“…To induce crush injury on the sciatic nerve, the previously described surgical procedure was performed (Byun et al, 2005; Lee et al, 2018). Right sciatic nerve was exposed by incision on the gluteal muscle under anesthesia using Zoletil 50 (50 mg/kg, intraperitoneally; Vibac Laboratories, Carros, France).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations